SNP array screening of cryptic genomic imbalances in 450 Japanese subjects with intellectual disability and multiple congenital anomalies previously negative for large rearrangements - Uehara, Daniela Tiaki; Hayashi, Shin; Okamoto, Nobuhiko; Mizuno, Seiji; Chinen, Yasutsugu; Kosaki, Rika; Kosho, Tomoki; Kurosawa, Kenji; Matsumoto, Hiroshi; Mitsubuchi, Hiroshi; Numabe, Hironao; Saitoh, Shinji; et al. (Journal of human genetics, 2016)
Intellectual disability (ID) is a heterogeneous condition affecting 2-3% of the population, often associated with multiple congenital anomalies (MCA). The genetic cause remains largely unexplained for most cases. To investigate the causes of ID/MCA of unknown etiology in the Japanese population, 645 subjects have been recruited for the screening of pathogenic copy-number variants (CNVs). Two screenings using bacterial artificial chromosome (BAC) arrays were previously performed, which identified pathogenic CNVs in 133 cases (20.6%; Hayashi et al., J. Hum. Genet., 2011). Here, we present the findings of the third screening using a single-nucleotide polymorphism (SNP) array, performed in 450 negative cases from our previous report. Pathogenic CNVs were found in 22 subjects (4.9%), in which 19 CNVs were located in regions where clinical significance had been previously established. Among the 22 cases, we identified PPFIA2 as a novel candidate gene for ID. Analysis of copy-neutral loss of heterozygosity (CNLOH) detected one case in which the CNLOH regions seem to be significant. The SNP array detected a modest fraction of small causative CNVs, which is explained by the fact that the majority of causative CNVs have larger sizes, and those had been mostly identified in the two previous screenings.